Hydro Magnetic Elastic Free Convection of a Conducting Elastico-Viscous Liquid Between Heated Vertical Plates - Reddy, P. Sreehari; Nagarajan, A. S.; Sivaiah, M. (Journal of Naval Architecture and Marine Engineering, 2009)
The natural convection flow of a conducting visco-elastic liquid between two heated vertical plates under the influence of a transverse magnetic field has been studied in this paper. Dimensionless equations of the problem have been solved by the method of successive approximation. Numerical solutions for velocity and temperature have been obtained. The results obtained are discussed with the help of graphs. The effect of magnetic parameter M, Visco-elastic parameter RC and the product of Prandtl and Eckert numbers [PE] on velocity and temperature fields are investigated Key words: Visco-elastic liquid, viscous dissipation, vertical plates, convection, successive approximation. DOI: 10.3329/jname.v5i2.2694 Journal of Naval Architecture and Marine Engineering 5(2)(2008) 47-56